(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is devoted to issues related to the nature, characteristics, and objectives of using Kyrgyz proverbs in Kyrgyz language lessons in accordance with modern requirements, which include the importance of considering proverbs as part of the Kyrgyz language lesson content. Additionally, proverbs are examined as expressive illustrative tools that represent complete artistic texts in terms of content